2021
DOI: 10.3390/s21072389
|View full text |Cite
|
Sign up to set email alerts
|

Fringe Projection Profilometry in Production Metrology: A Multi-Scale Comparison in Sheet-Bulk Metal Forming

Abstract: Fringe projection profilometry in combination with other optical measuring technologies has established itself over the last decades as an essential complement to conventional, tactile measuring devices. The non-contact, holistic reconstruction of complex geometries within fractions of a second in conjunction with the lightweight and transportable sensor design open up many fields of application in production metrology. Furthermore, triangulation-based measuring principles feature good scalability, which has l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…As a result, the data are epresented as a meshed 3D point cloud and stored in .STL-files. For a more detailed overview on the application of fringe projection metrology at various scales within production metrology, a comprehensive assessment is provided in [14].Within the scope of this study, different types of hairpin stators were inspected and reconstructed. The dimensions as well as specifications in terms of the power differentiated depending on the stator type.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the data are epresented as a meshed 3D point cloud and stored in .STL-files. For a more detailed overview on the application of fringe projection metrology at various scales within production metrology, a comprehensive assessment is provided in [14].Within the scope of this study, different types of hairpin stators were inspected and reconstructed. The dimensions as well as specifications in terms of the power differentiated depending on the stator type.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research analysed the performance and revealed the advantages of optical 3D metrology in different applications [14,24,25], and active vision sensors using an additional light source are particularly widespread due to improved robustness and accuracy [26]. Therefore, the development of 3D processing and spatial feature extraction algorithms is crucial.…”
Section: D Feature Extraction and Product Metrologymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the small blade root and the small depth difference of the plastic deformation, most industrial fringe projection sensors are not particularly suitable for this application. Many of these have a larger measuring volume, resulting in a low axial and lateral resolution related to this application [ 40 ]. Due to the smaller measuring volume, the borescopic sensor is applied here; however, other fringe projection sensors can also be used, considering the limitations with regard to resolution and measuring volume.…”
Section: Disassembly Of Turbine Bladesmentioning
confidence: 99%
“…A major challenge in the validation of these models is the detection of the voids. In contrast to defects close to the surface, which can be detected by imaging methods such as visual inspection, microscopy or fringe projection profilometry [10], the voids are located inside the component. One possibility for determining a void volume fraction is using computer tomography (CT).…”
Section: Introductionmentioning
confidence: 99%